Effect of the anatomical structure, wood properties and machining conditions on surface roughness of wood - Laina, Rubén; Sanz-Lobera, Alfredo; Villasante, Antonio; López-Espí, Pablo; Martínez-Rojas, Jose Antonio; Alpuente, Jesús; Sánchez-Montero, Rocío; Vignote, Santiago (Maderas. Ciencia y Tecnología, 2017)
The main aim is to test the influence of anatomical structure (grain direction and elements size), wood hardness and machining conditions on wood surface roughness. 180 samples defect-free were obtained from beech, oak and pine and processed with different machining methods (planning, sanding with 60 grit or sanding with 180 grit). Roughness, hardness, and anatomical structure were analysed using international methodologies. An analysis of variance of the data from all the samples with the four factors in the experimental design were performed. Results showed that machining processes and species are the factors that significantly affect surface roughness, as opposed to grain direction (plane of section and stylus-grain angle), which was only shown to be significant in some subgroups. Roughness parameters of samples sanded with 180 grit were lower in contrast to samples planned or sanded with 60 grit. Hardness was found to be the property of the wood that most clearly affects its final roughness, and makes it difficult to achieve better roughness results as the hardness increases.